2015
DOI: 10.1039/c4tc02224f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of long-range ordered, broccoli-like SERS arrays and application in detecting endocrine disrupting chemicals

Abstract: Periodic broccoli-shaped Au and Ag surface-enhanced Raman spectroscopy (SERS) arrays were fabricated by combining ordered SiO 2 colloidal crystal templates with the physical deposition technique. The SiO 2 colloidal crystal-assisted Au and Ag SERS substrates have a long-range, adjustable periodic structure and a clean surface without incorporating any reductants or surfactant chemicals. Different from depositing directly on the flat substrates, the colloidal crystal-assisted nanostructure array has a larger ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 80 publications
(133 reference statements)
2
28
0
Order By: Relevance
“…al. 26 have reported similar results. They showed that broccoli-shaped Ag deposited on SiO 2 colloidal crystal templates by physical deposition technique gives good enhancement.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…al. 26 have reported similar results. They showed that broccoli-shaped Ag deposited on SiO 2 colloidal crystal templates by physical deposition technique gives good enhancement.…”
Section: Introductionsupporting
confidence: 61%
“…N bulk =AhC bulk NA, where A is the area of the laser focal spot, h is the focal depth of the laser, and h is 13µm according to the work. 26 C bulk is the concentration of R6G bulk solution, here C bulk =10 -3 M, NA is the Avogadro constant surf ൌ ܸܰ ‫ܣ‬ ‫ݎߨ‬ ଶ The above calculations (see Fig.S11 †) were done for the 20 µl R6G solution (1x10 -3 M) and the R6G -absorbed on Ag@SiO 2 (1x10 -11 M, 20 µl) which were spread on the 1x1 cm 2 prepare substrate. A laser spot area of 5 µm and power of (15 mW) was applied with an accumulation number of 1sec for all recordings.…”
Section: ൌ ൈmentioning
confidence: 99%
“…The decrease in the peak intensity is related to the reduced number of the R6G molecules in the collection volume of the Raman spectroscope. The change in peak shape and the shift in peak position are related to the change in the chemical bonding of the R6G molecules due to interactions between the molecules and the environment [27,28]. The spectral intensity of R6G on annealed Ag@CuO thin films shows improved SERS performance as compared to the as prepared counterparts from Fig.…”
Section: Sers Of Ag@cuo Nanostructuresmentioning
confidence: 87%
“…1,2 As a molecule vibrational spectroscopy, the Raman technique showing abundant molecule information is highly suitable for the detection of complex pollutants. 3,4 For the SERS technology, one of the most important issues is substrate fabrication. A great progress has been achieved, but there are still challenges in the SERS substrate development.…”
Section: Introductionmentioning
confidence: 99%